Decoding iron deficiency in cancer: mechanisms, immune modulation, and therapeutic potential - Lin, Lihao; Yin, Xunzhe; Guan, Yi (Frontiers in Nutrition, 2025)
Iron is a vital micronutrient in many biological functions, including DNA metabolism, oxygen transport, and cellular energy generation. In this context, it is intimately linked to cancer biology. However, although many studies have comprehensively investigated and reviewed the effects of excess iron on tumor initiation and progression, the potential interrelations of iron deficiency with tumors have been largely neglected and need to be better defined. Recent studies have highlighted the complex relationship between iron deficiency and tumor biology. Iron deficiency in specific tumor types can promote tumor progression through activation of hypoxic responses, metabolic reprogramming, and suppression of the immune response, as well as inhibit tumor growth by limiting tumor cell proliferation, among other mechanisms. This review aims to systematically explore the dual mechanisms of iron deficiency in tumors, its specific effects in different tumor types, its impact on tumor metabolism, immune responses, and therapy, and its prospects as a potential therapeutic target. Furthermore, the potential of iron metabolism markers in tumor diagnosis and prognosis is discussed. By synthesizing existing evidence, this paper comprehensively explains how iron deficiency affects tumorigenesis and identifies future research and clinical practice directions.